The effectiveness of FRCM-U-wrap joist: An alternative solution in flexural strengthening of reinforced concrete beams. Issue 3 (1st February 2021) - Anania, Laura
Abstract: This paper presents both experimental and analytical research results for predicting the enhancement of the flexural capacity of reinforced concrete (r.c.) beams strengthened in flexure with an innovative system based on the use of fabric reinforced cementitious matrix (FRCM). The patented system, called FRCM-U-Wrap Joist Tech provides a new methodology for beam strengthening capable of generating a higher internal couple of the cross section with no incisive change of the element weight. Experimental evidence gives back a 100% of increase in flexural strength than the non-reinforced beam. Analytical prediction shows a good accordance with the experimental data. The proposed strengthening system seems to be more effectiveness than the beam strengthened by means of traditional technology consisting in externally bonding the fibers directed to the beam intrados.